1997
DOI: 10.2134/jeq1997.00472425002600020028x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Composition of Fertilizers and Soil Amendments

Abstract: The use of fertilizers and soil amendments has raised concern regarding the toxic accumulation of their trace components in the environment. The objective of this research was to evaluate the trace element and heavy metal composition of a wide variety of fertilizers and soil amendments. Thirty‐five elements, including priority pollutants, were determined in 24 materials. A microwave HNO3‐HF‐H2O2‐H3BO3 digestion procedure was used to dissolve the samples. Selected solid samples were directly analyzed by neutron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
4
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(91 citation statements)
references
References 0 publications
8
69
4
10
Order By: Relevance
“…(Brasil 2005) em Pontos distribuídos ao longo do curso do rio (P3, P7, P8, P9, P11, P12, P13). Atividades antropogênicas que podem adicionar Ni e Pb aos solos e, por conseguinte, à água são: mineração, adubação com lodo de estação de tratamento de efluentes (Page et al 1972, Alloway & Ayres 1997, fabricação de baterias de automóveis e celulares, estabilização de plásticos, formulação de pigmentos, fertilizantes fosfatados (Prasad 1995, Loganathan 1997, Raven & Loeppert 1997 e queima de combustíveis fósseis (Alloway & Ayres 1997), dentre outros.…”
Section: Discussionunclassified
“…(Brasil 2005) em Pontos distribuídos ao longo do curso do rio (P3, P7, P8, P9, P11, P12, P13). Atividades antropogênicas que podem adicionar Ni e Pb aos solos e, por conseguinte, à água são: mineração, adubação com lodo de estação de tratamento de efluentes (Page et al 1972, Alloway & Ayres 1997, fabricação de baterias de automóveis e celulares, estabilização de plásticos, formulação de pigmentos, fertilizantes fosfatados (Prasad 1995, Loganathan 1997, Raven & Loeppert 1997 e queima de combustíveis fósseis (Alloway & Ayres 1997), dentre outros.…”
Section: Discussionunclassified
“…Also, since most growth promoters contain metals, their use in animal production may elevate concentrations of these elements in manure (Nahm 2002). Raven and Loeppert (1997) suggested that the potential environmental hazard of toxic levels of trace elements in organic amendments depended on the elemental composition of the material, the fraction of the constituent element that is released, the mobility and toxicity of the released elements in the environment and the ease of incorporation of toxic elements into the biota. Further, they felt that the total elemental composition of a material (as measured in our study) can give a preliminary view of its potential for environmental contamination, and when composition and application rates are taken into account, an estimate of the maximum possible pollution caused through the use of a material can be determined.…”
Section: Trace Elementsmentioning
confidence: 99%
“…그러나 식물은 과도하게 흡수된 카드뮴 의 독성을 최소화하기 위해 다양한 생리 ․ 생화학적 방어시스템을 가동하여 식물독성을 극복하고자 한다 (Raven and Loeppert, 1997;Salt et al, 1995). 카드뮴에 의해 유도된 활성산소종의 소거는 항산화효소 (superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), glutathione reductase (GR))에 의한 효소 적인 소거와 항산화제 (ascorbate (AsA), glutathione (GSH))에 의한 비효소적 소거를 기반으로 한, 무독화 시스템이 생체 내의 주요한 활성산소종 소거전략으로 정설화되어 있다 (Gill and Tuteja, 2010;Talukdar, 2012;Zhang et al, 2013).…”
Section: Introductionunclassified